Recovery of high quality water from human urine using a novel vertical up-flow forward osmosis reactor. (June 2021) - Patel, Asfak; Mungray, Arvind Kumar; Mungray, Alka
Graphical abstract: Highlights: Water was recovered from neat human urine using a novel VUF-FO reactor. System was operated without any control over the pH for five days. Pulsating inlets were used in the reactors to mitigate the membrane fouling. Distillation without membrane was used to recover water. Recovered water was matched with the drinking water standards. Abstract: Nutrients in human urine are very much diluted which increases the cost of transportation for the direct use or increases the cost of treatment processes for the recovery of nutrients. In this work, a novel Vertical Up-Flow Forward Osmosis (VUF-FO) reactor with pulsating inlets was used for the separation of water and for concentrating nutrients from fresh human urine. The performance was compared with the basic H-shape FO reactor for the water flux, membrane fouling and rejection efficiencies of the constituents. After the three days of the process, only a 10% decrease in water flux was observed for the VUF-FO reactor compared to 50% decrease in the case of H-shape FO reactor. Less membrane fouling was observed in the VUF-FO reactor due to the vertical arrangement with the pulsating inlets compare to H-shape reactor. A simple distillation process without membrane was used for the recovery of water from the diluted draw agent. The combination of FO and distillation showed a 100% rejection of chemical oxygen demand (COD) and biochemical oxygen demand (BOD) in the recovered water. The quality of separated water from the urine was comparable with reverse osmosis (RO) water and satisfied the Indian Standards for drinking water.